Rancang Bangun Aplikasi Naskah Dinas Elektronik Berbasis Web Menggunakan WDLC - Nur Annisa Kadarwati Febriyani; Raden Budiarto Hadiprakoso (Universitas Multimedia Nusantara, 2021)
In the modern era of technological development, the application of electronic official script management is a solution to the administrative and communication challenges of agencies during the pandemic, such as today, where administrative work needs to be done from home (work from home). With the condition of a high level of need, the management of official manuscripts in the XYZ organization still uses conventional methods. So, this raises obstructed letter distribution and loss documents problem, and waste of paper use. We propose the Electronic Service Manuscript Management Application to replace the official script management process that previously applied conventional methods to using electronic methods to solve this problem. Besides, we also implement security aspects in the SHA-512 algorithm to fulfill authentication, AES-128 to meet confidentiality, and RSA2048 to meet integrity and non-repudiation. Apart from the security aspect, functionally, the system is built based on the Guidelines for Electronic Service Manuscripts, which are tailored to the organization's needs. The system development uses the Web Development Life Cycle (WDLC) methodology using the Yii2 framework. From the research results, it is concluded that the Electronic Service Manuscript Management Application has been built according to the needs of the organization and can be a security alternative in the official script management process. Index Terms—digital signature; encryption; official script management; WDLC